2010
DOI: 10.1161/circep.110.951525
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Coronary Arteries in Areas Involved in Atrial Fibrillation Catheter Ablation

Abstract: Background-The proximity to vascular structures is a limiting factor during radiofrequency ablation. However, little or no attention has been given to the atrial arterial circulation during the development of atrial fibrillation (AF) catheter ablation techniques. Methods and Results-We examined the atrial arterial circulation in areas involved in AF ablation in 24 heart specimens by colored resin injection and careful dissection. The sinus node artery (SNA) arose from the circumflex artery in 42% of case; prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…[3][4][5] In addition, the cooling effect of arterial and endocardial blood flow may limit lesion formation and success of the procedure. 6,7 …”
mentioning
confidence: 99%
“…[3][4][5] In addition, the cooling effect of arterial and endocardial blood flow may limit lesion formation and success of the procedure. 6,7 …”
mentioning
confidence: 99%
“…The location of the SA node is well recognized; however, anatomical variation particularly with its arterial supply is not as well appreciated . It has been shown that major atrial coronary arteries are commonly found in areas typically targeted in AF ablation . This includes the SA nodal artery, which can arise from the circumflex artery in 40% of individuals and can thus be susceptible to injury during LA ablation, such as PVI, or creation of a roof or mitral‐isthmus line.…”
Section: Mechanisms Of Sndmentioning
confidence: 99%
“…[6][7][8] In addition, the cooling effect of arterial and endocardial blood flow may limit lesion formation and success of the procedure. 9,10 Editorial see p 573 Clinical Perspective on p 733…”
mentioning
confidence: 99%